Importance of high power factor in thermoelectric materials for power generation application: A perspective - Liu, Weishu; Kim, Hee Seok; Jie, Qing; Ren, Zhifeng (Scripta materialia, 2016)
[Display omitted] The figure of merit (ZT) has been used for more than half a century to guide the research of thermoelectric materials. In this perspective viewpoint, we emphasize that the power factor (PF) is more important than the thermal conductivity for thermoelectric power generation for a given ZT. We also propose the newly defined engineering parameters (ZT)eng and (PF)eng are the more practical indicators to show the temperature dependent efficiency and output power, as compared with conventional ZT and PF.